Understanding the immune responses in granuloma formation through agent-based simulation - Al Haek, Mohammed; Ismail , Amelia Ritahani (2014)
Granuloma formation is a medical condition that occurs as a result of infection of bacteria to the host, which include getting rid of unwanted substances, destroying pathogen, enhancing immunity by stimulating the macrophages following the T-lymphocytes contained in it. Granuloma appears in diseases such as Mycobacterium Tuberculosis and Visceral Leishmaniasis. Although granuloma is a host-defense mechanism for containing bacteria, it also contribute to early bacterial growth and shelters the bacteria thus they can spread later and it might be harmful.